Delayed graft function is associated with an increased rate of renal allograft rejection: A retrospective single center analysis - Weber, Susanne; Dienemann, Thomas; Jacobi, Johannes; Weidemann, Alexander; Eckardt, Kai-Uwe (PLoS ONE, 2018)
INTRODUCTION: The association of delayed graft function (DGF) and biopsy proven acute rejection (BPAR) of renal allografts is controversial. Borderline rejections comprise a major portion of biopsy results but the significance of such histologic changes is debated. The present study explores the impact of DGF on BPAR with a special emphasis on discriminating the effects of borderline rejection. METHODS: Single center analysis of 417 deceased donor kidney recipients (age>18; transplantation date 1/2008-2/2015). Patients with primary non-function were excluded. DGF was defined as the need for dialysis within the first week after transplantation. Acute rejection was defined according to Banff criteria. Cox proportional hazards models were used to examine the relationship of DGF with BPAR within the first year. RESULTS: No graft loss was observed during the first year after transplantation. DGF significantly associated with BPAR in the first year, irrespective of whether borderline rejections were included (HR 1.71, 95%CI 1.16,2.53) or excluded (HR 1.79, 95%CI 1.13,2.84). CONCLUSION: DGF is significantly associated with rejection-with or without borderline changes-within the first year.
EVALuna2:34513